Evidentiary Proceedings in Indonesian Criminal Procedure Law and the Jinayat Procedural Law Concerning Electronic Evidence. - Khalisah Dinah Muniati; Mohd. Din; Yanis Rinaldi (International Journal of Law, Crime and Justice, 2026)
Technological advancement in information systems has significantly transformed the criminal evidentiary framework by positioning electronic evidence as an increasingly essential instrument in proving criminal acts. Indonesian Criminal Procedure Law, particularly Law Number 20 of 2025 on Criminal Procedure, explicitly recognizes electronic evidence as lawful evidence with equal standing to conventional forms of evidence. In Aceh, recognition of electronic evidence is also embedded within the Aceh Qanun Number 7 of 2013 on Jinayat Procedure Law, which accommodates electronic information and recordings through the concept of qarinah (circumstantial evidence). Nevertheless, differences remain in regulatory frameworks and evidentiary standards between the national criminal procedure system and the jinayat procedural system, potentially leading to divergences in evidentiary assessment. Such disparities may affect the implementation of legal certainty and justice within judicial practice in Aceh. This study aims to examine the legal position of electronic evidence under the Jinayat Procedural Law and Law Number 20 of 2025 on Criminal Procedure, to analyze the differences in evidentiary standards applied in both legal systems, and to assess their implications for the principles of justice and legal certainty. The research employs a normative juridical method using statutory and conceptual approaches. Data were collected through library research involving primary, secondary, and tertiary legal materials related to electronic evidentiary rules, and were analyzed using qualitative descriptive techniques. The findings indicate that Law Number 20 of 2025 grants electronic evidence an independent evidentiary status, provided that requirements such as authenticity, integrity, system reliability, and lawful acquisition are fulfilled. In contrast, the Jinayat Procedural Law integrates electronic evidence within the framework of qarinah, where its use is guided by Islamic legal principles, particularly in ta’zir offenses. These differing standards result in variations in how electronic evidence is evaluated within general courts and sharia courts in Aceh. Consequently, there is a need for harmonization between national criminal procedural law and jinayat procedural law, the development of more comprehensive technical guidelines, and the strengthening of digital forensics practices within the Sharia Courts to ensure legal certainty, justice, and effective proof without disregarding Islamic legal principles